Toward a Definition of the Linguistic Profile of Children With Autism Spectrum Disorder - Marini, Andrea; Ozbič, Martina; Magni, Rita; Valeri, Giovanni (Frontiers in Psychology, 2020)
The current investigation assessed linguistic and narrative abilities in a cohort of children with Autism Spectrum Disorder (ASD). The linguistic assessment was performed with both traditional tests and a multilevel procedure for discourse analysis. The results showed difficulties at different stages of message planning, organization, and microlinguistic processing (i.e., lexical selection and grammatical processing). Their macrolinguistic impairments were likely related to more general difficulties in the prelinguistic conceptual phase of message planning and mental model generation. Such weaknesses included a difficulty in the non-verbal conceptualization of the story and the generation of an internal representation of the addressee’s mental model.